The ion channel CALHM6 controls bacterial infection‐induced cellular cross‐talk at the immunological synapse. (2nd March 2023) - Danielli, Sara; Ma, Zhongming; Pantazi, Eirini; Kumar, Amrendra; Demarco, Benjamin; Fischer, Fabian A; Paudel, Usha; Weissenrieder, Jillian; Lee, Robert J; Joyce, Sebastian; Foskett, J Kevin; Bezbradica, Jelena S
Abstract: Membrane ion channels of the calcium homeostasis modulator (CALHM) family promote cell–cell crosstalk at neuronal synapses via ATP release, where ATP acts as a neurotransmitter. CALHM6, the only CALHM highly expressed in immune cells, has been linked to the induction of natural killer (NK) cell anti‐tumour activity. However, its mechanism of action and broader functions in the immune system remain unclear. Here, we generated Calhm6 −/− mice and report that CALHM6 is important for the regulation of the early innate control of Listeria monocytogenes infection in vivo . We find that CALHM6 is upregulated in macrophages by pathogen‐derived signals and that it relocates from the intracellular compartment to the macrophage‐NK cell synapse, facilitating ATP release and controlling the kinetics of NK cell activation. Anti‐inflammatory cytokines terminate CALHM6 expression. CALHM6 forms an ion channel when expressed in the plasma membrane of Xenopus oocytes, where channel opening is controlled by a conserved acidic residue, E119. In mammalian cells, CALHM6 is localised to intracellular compartments. Our results contribute to the understanding of neurotransmitter‐like signal exchange between immune cells that fine‐tunes the timing of innate immune responses. Synopsis: CALHM6 is an immune synaptic ion channel that regulates the kinetics of natural killer (NK) cell activation during infection. Pro‐inflammatory stimuli like Poly(I:C) and systemic Listeria monocytogenes infection activate macrophages to upregulate CALHM6 expression. Infected macrophages activate NK cells in the spleen through the formation of an immunological synapse to which CALHM6 is recruited. In Calhm6‐deficient mice infected with L. monocytogenes, the production of IFN‐γ and IL‐10 from NK cells is delayed and the initial bacterial burden increased. Mouse CALHM6 expression in the membrane of Xenopus oocytes is toxic as the channel is constitutively open. Cells with reduced or transient mCALHM6 expression generate ion currents dependent on the conserved negatively charged residue E119. Abstract : CALHM6 fine‐tunes the timing of innate immune responses by regulating ATP release at the immunological synapse to control NK cell activation.